The effects of advertiser-web site congruity on the responses to advertising and the mediating role of emotions - Mermari, Houda; Bahoussa, Abdelaziz (International Journal of Engineering and Technology, 2019)
This exploratory research aims to study how the effect of perceived congruence between advertising and the website, in the online context, affects the attitudes of Moroccan Internet users (consumers) and consequently their behavior towards advertisers and publishers. The goal, more specifically, is to identify the effect of congruence and incongruence between advertising and its context (support) on advertising responses in order to better understand which approach is most effective in our context. And also identify the factors that interact in this relationship. Through an experiment, we explored the field. The results are presented and commented on in this article.Â